The evaluation of the National Partnership Project in England: Processes, issues and dilemmas in commissioned evaluation research - Campbell, A; McNamara, O; Furlong, J; Lewis, S; Howson, J (2007)
This article reviews the processes, issues and dilemmas involved in evaluation research undertaken in the context of changing and evolving government policy in education. The article is grounded in an evaluation of the National Partnership Project (NPP), the team conducted on behalf of England's Teacher Training Agency (TTA) in 2004-2005. It will not present a critique of partnership in England, but will draw on perspectives of partnership to provide some background information to the project. It will also discuss the processes of evaluation research in the context of frameworks from recent and relevant research and will raise issues for future commissioned evaluation research to address.